MENCERMATI PERAN AGAMA DAN KEPERCAYAAN MASA KINI: ANTARA “MENGATASI MASALAH” (PROBLEM SOLVING) ATAU “SUMBER MASALAH”(SOURCE OF PROBLEM) - Marthinus Marcel Lintong (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2020)
The main focus of this article is criticizing the role of today’s belief and religion in the context of human relationship. Belief and religion sociologically were people’s creations to perform the influence of such a supernatural power and domination over human’s life. Over centuries, religious beliefs and people’s convictions have inspired and illuminated many people of any civilizations to pursue or gain some values, ideas and truth through their special way of living by creating laws, rules, scriptures and any traditions specified to them. At the same time, world’s history have clearly noted the two paradoxal sides of belief and religion. In one side, belief and religion offer values, ideas, laws and norms to order human’s life to have a good religious life. But in the other side, they showed a long story of cruelties, wars, bloodshed and any radical movements on behalf of any religions or religious sects. This writing is meant to describe more obviously these “two opposite faces” of belief and religion and gave an offer to readers to make a self reflection and then take a proper and objective way of thinking by regarding to some tragic events like WTC tragedy in US seventeen years ago (2001) or to any other like event that happened surround us recently. Conclusively, we might see that for men or women, religion and belief could stand in any way as a “problem solving” or “problem sourcing”. They were hoped and suggested to offer or create peacefullness, charity and well being conditions, but in any way they become also a source or ignition of wars, cruelties and social revolution that seemed to have no end until now.